Le « Héros homicide et nocturne » en pleines « Lumières » : de Cartouche ou les voleurs (1721) aux « Vies privées » (1721-1803) - Anne-Marie Mercier-Faivre (Criminocorpus)
The eighteenth century in France is a time of questioning of the judicial system. With justice being dispensed in camera, the “court of public opinion” attempts to assert a role in the quest for truth. The movement, revealed in the plays La Devineresse (1679) by Thomas Corneille and Cartouche et les voleurs (1721) by Legrand, shows a curiosity that goes beyond the spectacle of criminal executions. If Corneille’s play is used by the authorities to attack superstition in the “poisons affair”, the decision to forbid Legrand’s play (presenting the criminal Cartouche in a very attractive light at the moment of his trial) shows that the government is taking note of the new fascination with criminals. Public interest in judicial questions subsequently turns towards judicial mémoires and towards “Vies privées” or “Private Lives”: these publications develop originally around criminal figures and become common in the political sphere after the 1780s. The way in which the character of the criminal shifts between the different genres reveals his theatrical aspect and paradoxically at the same time the questions this poses for the theatrical genre.